2002
DOI: 10.1122/1.1446883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shear flow on a polymeric bicontinuous microemulsion: Equilibrium and steady state behavior

Abstract: SynopsisWe have investigated the effects of shear flow on a polymeric bicontinuous microemulsion using neutron scattering, light scattering, optical microscopy, and rheology. The microemulsion consists of a ternary blend of poly͑ethyl ethylene͒ ͑PEE͒, poly͑dimethyl siloxane͒ ͑PDMS͒, and a PEE-PDMS diblock copolymer. At equilibrium, the microemulsion contains two percolating microphases, one PEE rich and the other PDMS rich, separated by a copolymer-laden interface; the characteristic length scale of this struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 56 publications
6
65
1
Order By: Relevance
“…At low temperatures, the behavior of the BmE approaches that of the diblock (and PCHE homopolymer), consistent with a morphology of two 3-dimensional interpenetrating networks of well-segregated domains enriched with each homopolymer (Fig. [43][44][45]48 Similarities in the frequency dependence of the linear viscoelastic properties of the BmE and the pure disordered PCHE-PE-14 diblock, evident in the time-temperature superposed master plots (Fig. However, with increasing temperature the opposite trend is evident, where at the highest measurement temperatures the viscosity of the BmE more closely resembles that of the PE homopolymer.…”
Section: Dynamicssupporting
confidence: 57%
See 2 more Smart Citations
“…At low temperatures, the behavior of the BmE approaches that of the diblock (and PCHE homopolymer), consistent with a morphology of two 3-dimensional interpenetrating networks of well-segregated domains enriched with each homopolymer (Fig. [43][44][45]48 Similarities in the frequency dependence of the linear viscoelastic properties of the BmE and the pure disordered PCHE-PE-14 diblock, evident in the time-temperature superposed master plots (Fig. However, with increasing temperature the opposite trend is evident, where at the highest measurement temperatures the viscosity of the BmE more closely resembles that of the PE homopolymer.…”
Section: Dynamicssupporting
confidence: 57%
“…[43][44][45][46][47][48][49][50][51] Linear viscoelastic studies have shown that the BmE morphology has ''excess'' viscosity and elasticity arising from the structured nature of the fluid, similar to the behavior of sponge phases, 52,53 liquid crystal based blue phases, 54,55 and worm-like micelles. [43][44][45][46][47][48][49][50][51] Linear viscoelastic studies have shown that the BmE morphology has ''excess'' viscosity and elasticity arising from the structured nature of the fluid, similar to the behavior of sponge phases, 52,53 liquid crystal based blue phases, 54,55 and worm-like micelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the rather simple principle of Couette flow provides a tremendous range of applications, e.g., in lubricants in sleeve bearings, for blood dialysis in medical science [1][2][3], emulsion polymerization [34], polymerization of blends [39] etc. For experimental investigations of effects of shear flow on polymeric solutions and bicontinuous microemulsions we refer to [37]. The observations specified therein nicely represent our simulation results.…”
Section: Couette Flowsupporting
confidence: 66%
“…The blends of narrow molecular weight distribution ( w / n 1.1) poly(ethyl ethylene) (PEE) with poly(dimethylsiloxane) (PDMS) were compatibilized with their diblock copolymer: PEE/PDMS/PEE-PDMS; the polymer molecular weight of the was: 1.71, 2.13, and 10.4 (w PEE 0.52) kg mol 1 , respectively [252,253]. The dynamic and steady shearing tests were carried out at 15-30 C -the -superposition principle was not obeyed.…”
Section: Influence Of Rheology On Thermodynamicsmentioning
confidence: 99%